EFFECT OF LIGHT COLORS TO EXPLOIT FLY SQUID (STHENOTEUTHIS OUALANIENSIS LESSON, 1830) WITH STICK-HELD FALLING NET - Hải, Nguyễn Văn (Vietnam Journal of Marine Science and Technology, 2014)
In 2011, two offshore-survey trips was conducted in Central part using underwater lights of 170 hauls of squid, in which 3 kinds of color are yellow - green - white used. On average, each night 7 hauls was performed in order to ensure that each must be made at least 30 hauls with each haul takes 1 hour. The results indicate that the highest productivity in white and lowest in yellow, there is a significant difference between those lights, in contrast, the others lights showed insignificant difference at the P <0.05 level. There is no significant difference on average length of exploited squids among lights (P <0.05).